Breast and reproductive cancers in the transgender population: a systematic review. (29th May 2018) - Joint, R; Chen, ZE; Cameron, S
Abstract : Background: The medical transition undergone by a transgender person may influence their risk of breast or reproductive cancer. Objectives: To assess breast and reproductive cancer prevalence in the transgender population. To elucidate any associations between gender‐affirming hormones and risk of these cancers. Search strategy: Following registration of review protocol with PROSPERO, five databases were searched. Selection criteria: Included studies investigated breast, ovarian, uterine, cervical, vaginal, neovaginal, testicular and prostate cancer in the transgender population. Secondary studies, opinions, editorials and conference abstracts were excluded. No date, language or setting restrictions were applied. Data collection and analysis: Two reviewers conducted literature searches and applied inclusion and exclusion criteria to the results. Studies were categorised, aggregated and analysed by study population (transmen/transwomen) and type of cancer. Main results: The literature search produced 228 articles; 43 were included. The overall evidence quality was very low to low. In transgender women, 20 breast cancer cases, two neovaginal cancer cases, one testicular cancer case and eight prostate cancer cases were reported. In transgender men, 18 breast cancer cases, five ovarian cancer cases, four uterine/cervical cancer cases and one vaginal cancer case were reported. Conclusions: There is insufficient evidence to estimate breast or reproductive cancer prevalence in the transgender population. Gender‐affirming hormones have not been shown to affect cancer risk, but there is a clear need for well‐designed, robust studies to confirm or refute this. Funding: This study was undertaken as an education dissertation. No funding was received. Tweetable abstract: Little is known about the impact of gender‐affirming hormones on breast or reproductive cancers in trans people. Tweetable abstract: Little is known about the impact of gender‐affirming hormones on breast or reproductive cancers in trans people.